2007
DOI: 10.1007/s00425-007-0595-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of season-long high temperature growth conditions on sugar-to-starch metabolism in developing microspores of grain sorghum (Sorghum bicolor L. Moench)

Abstract: High temperature stress-induced male sterility is a critical problem in grain sorghum (Sorghum bicolor L. Moench) that significantly compromises crop yields. Grain sorghum plants were grown season-long under ambient (30/20 degrees C, day-time maximum/night-time minimum) and high temperature (36/26 degrees C) conditions in sunlit Soil-Plant-Atmospheric-Research (SPAR) growth chambers. We report data on the effects of high temperature on sugar levels and expression profiles of genes related to sugar-to-starch me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
116
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(135 citation statements)
references
References 65 publications
(109 reference statements)
17
116
1
1
Order By: Relevance
“…In addition, morphological characters such as stigma hyperplasia and stamen hypoplasia can result in failure of pollination (contact of pollen with stigma) and the fertilisation process (Takeoka et al 1991). Changes in composition and concentrations of carbohydrates (Jain et al 2007), lipids and reactive oxygen species (Djanaguiraman et al 2013a(Djanaguiraman et al , 2013b(Djanaguiraman et al , 2014 in pollen gains result in pollen sterility. Additional research is required to test these principles in wheat.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, morphological characters such as stigma hyperplasia and stamen hypoplasia can result in failure of pollination (contact of pollen with stigma) and the fertilisation process (Takeoka et al 1991). Changes in composition and concentrations of carbohydrates (Jain et al 2007), lipids and reactive oxygen species (Djanaguiraman et al 2013a(Djanaguiraman et al , 2013b(Djanaguiraman et al , 2014 in pollen gains result in pollen sterility. Additional research is required to test these principles in wheat.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the analysis of carbohydrate content in chickpea flowers subjected to cold stress revealed a reduction in carbohydrate levels in aborted styles and ovaries compared to those retained in the plant (Nayyar et al, 2005). Recently, Jain et al (2007) found a disruption in cell wall invertase activity under low temperature stress not only during the commonly reported pollen developmental phase but also in the stigma and the style. Taken together, these findings point out to a plausible effect of temperature stress on the sporophytic structures of the pistil and warrant further research.…”
Section: Female Development: the Pistil And The Female Gametophytementioning
confidence: 98%
“…A c c e p t e d M a n u s c r i p t 9 turnover in developing pollen grains, and, hence, lower accumulation of soluble carbohydrates (Aloni et al, 1991;Jain et al, 2007;Oliver et al, 2005;Pressman et al, 2002;Sato et al, 2002). A complete understanding of temperature stress on pollen development must await further understanding of carbohydrate turnover during this phase.…”
Section: Page 9 Of 24mentioning
confidence: 99%
“…PAS-positive polysaccharides were found in the mature pollen grains cytoplasm in Mercurialis annua and Ricinus communis (Franchi et al 1996), and in Trachycarpus fortunei . Soluble polysaccharides are also found in mature starchless pollen grains, but they are only detected using other methodologies, especially biochemical analyses (O'Brien & McCully 1981;Pacini 1996;Castro & ClĂ©ment 2007;Speranza et al 1997;Jain et al 2007). Speranza et al (1997) and ClĂ©ment & Pacini (2001) demonstrated that, for different species, the PAS-positive cytoplasm of the vegetative cells is closely related to pollen grains dehydration at the time of their release, which presents a great viability after they are released, and are always associated with a dry environment.…”
Section: Resultsmentioning
confidence: 99%